Reporting tendencies of child maltreatment within a UK based sample of the general population - Wright, Robyn (2018)
Objective: The aim of the study was to explore the association between demographic variables and the intentions to report child maltreatment. Participants: A convenience sample of 241 participants from the general population were recruited. All participants were over the age of 18, located within the UK and had internet access.